PERANCANGAN SISTEM INFORMASI SURAT MASUK DAN SURAT KELUAR BERBASIS WEB PADA KANTOR DESA CIKANDE PERMAI - Arief, Rahadian; Sapaatullah, Asep; Ardiansyah, Ardiansyah (LPPM Universitas Bina Bangsa, 2023)
Utilization of information and communication technology (ICT) has now become a major facility in various sectors of life and has become an inseparable part of daily human needs and activities. A good village office must have a system that can be used to support the performance of the village office. At the Cikande Permai Village office, there are difficulties in managing letters, making letters is still manual, namely making in word, recording incoming and outgoing letters is still using manually, namely by recording in a ledger and there are still many obstacles in its management such as losing letters, damaged stationery.The programming language to create this system uses the PHP programming language with MYSQL database, the research method used is the Flow Map method, DFD (Data Flow Diagram) with waterfall development, while the data collection techniques used in this research are interviews, observation and literature study.With this web-based incoming and outgoing mail information system, it is hoped that it will make it easier to write letters, record letters, archive letters and report letters